WEDI ISIN (TAKUT MALU); AJINING DIRI (HARGA DIRI) ORANG JAWA DALAM PERSPEKTIF WONG CILIK (RAKYAT JELATA) - Moh Soehadha (Religi: Jurnal Studi Agama-agama, 2014)
This article discuss self-esteem, one of  the Javanese attitude. Dignity or self- esteem for the Javanese is part of  the humanist character. Self-esteem is related to humanity (kamanungsan), namely the attitude of the self that prioritizes human behavior in treating others. Anthropologically, the Javanese self-esteem can be seen from the concept of local knowledge, which is a form of local knowl- edge that comes from daily life that is still growing in Java. The Javanese emic concept of self-esteem can be transformed into a value of wisdom and the spiri- tual insight on the present, when there is a stagnation in the application of general knowledge that has been dominated by Western values.